Research Trends in Islamic Religious Education and Students’ Emotional Management: A Scopus-Based Bibliometric Study - Farhana, Laila Nadia; Wibowo, Heru (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2026)
This study responds to the growing need to address students’ emotional well-being within educational contexts, particularly through value-based approaches such as Islamic Religious Education (IRE). Despite increasing attention to emotional development in education, global research integrating emotional management with IRE remains limited and fragmented. This study aims to map and analyze global research trends related to Islamic Religious Education and students’ emotional management using a Scopus-based bibliometric approach. Data were collected from the Scopus database and systematically screened using the PRISMA framework. A total of 4,368 documents published between 2014 and 2024 were analyzed using Biblioshiny in RStudio to examine publication trends, leading authors, influential journals, subject areas, collaboration networks, and emerging research themes. The findings reveal a significant increase in publications on students’ emotions over the past decade. However, studies that explicitly integrate emotional management within the context of IRE remain scarce. The field continues to be dominated by Western scholars and psychological perspectives, while contributions from Islamic educational contexts are relatively underrepresented. The analysis further identifies emotion regulation and motivation as emerging themes with strong potential for future research. These findings highlight the need to strengthen interdisciplinary and value-based research within IRE by integrating emotional and spiritual dimensions into educational practice. This study provides a comprehensive reference for future research and contributes to the development of a more holistic approach to promoting students’ emotional and spiritual well-being. Abstrak: Studi ini menanggapi semakin pentingnya memperhatikan kesejahteraan emosional siswa dalam konteks pendidikan, khususnya melalui pendekatan berbasis nilai seperti Pendidikan Agama Islam. Namun, penelitian global yang mengintegrasikan manajemen emosi dengan Pendidikan Agama Islam masih terbatas dan terfragmentasi. Studi ini bertujuan untuk memetakan dan menganalisis tren penelitian global dalam Pendidikan Agama Islam dan manajemen emosi siswa menggunakan pendekatan bibliometrik berbasis Scopus. Data dikumpulkan dari basis data Scopus dan disaring secara sistematis menggunakan kerangka kerja PRISMA. Sebanyak 4.368 dokumen yang diterbitkan antara tahun 2014 dan 2024 dianalisis menggunakan Biblioshiny di RStudio untuk meneliti tren publikasi, penulis terkemuka, jurnal berpengaruh, bidang studi, jaringan kolaborasi, dan tema penelitian yang muncul. Hasilnya menunjukkan peningkatan signifikan dalam publikasi yang berkaitan dengan emosi siswa selama dekade terakhir. Namun, studi yang secara eksplisit mengintegrasikan manajemen emosi dengan Pendidikan Agama Islam masih terbatas. Bidang ini didominasi oleh para sarjana Barat dan perspektif psikologis, sementara kontribusi dari konteks pendidikan Islam kurang terwakili. Analisis ini juga mengungkapkan bahwa regulasi emosi dan motivasi merupakan tema-tema yang muncul dengan potensi penelitian yang kuat. Temuan ini mengimplikasikan perlunya penguatan penelitian interdisipliner dan berbasis nilai dalam Pendidikan Agama Islam, khususnya dengan mengintegrasikan dimensi emosional dan spiritual ke dalam praktik pendidikan. Studi ini memberikan referensi komprehensif untuk penelitian masa depan dan berkontribusi pada pengembangan pendekatan yang lebih holistik terhadap kesejahteraan emosional dan spiritual siswa.